Assessing and understanding non-responsiveness of maize and soybean to fertilizer applications in African smallholder farms - Roobroeck, D.; Palm, Cheryl A.; Nziguheba, G.; Weil, R.; Vanlauwe, Bernard (Elsevier, 2021)
Use of mineral fertilizers is essential to enhance crop productivity in smallholder farming systems of Sub-Saharan Africa, but various studies have reported ‘non-responsiveness’ where application of inorganic fertilizers does not lead to satisfactory yield gains. This phenomenon is not well defined nor are its extent and causes well understood. In order to close these knowledge gaps, we assessed the effects of commonly recommended nitrogen (N), phosphorus (P) and/or potassium (K) fertilizer inputs on maize grain and soybean production on farmer fields across prevalent land slope and/or soil texture gradients (2 × 2 matrix) in four agroecosystems over two growing seasons. The extent of the problem in the two cropping systems was compared by decomposing frequency distributions into various ranges of fertilizer effect sizes that represent specific degrees of non-responsiveness and responsiveness. Key soil properties and rainfall variables for field trials were also determined to identify the factors that are limiting crop yield increases by mineral fertilizer input.